Discourse and ideology in Nabokov's prose - Larmour, David H. J. (David Henry James), 1959- (Studies in Russian and European literature ;, 2003)
These essays offer readings of several of Nabokov's novels, as well as discussions of his exchange of views about literature with Edmund Wilson, and his place in the 1960s and contemporary popular culture.